A Critical Analysis of Educationally Backward Block (EBB) Schools of Mizoram: A Case Study - Lalramnghaka, TBC; Chaurasia, Prateek (Voices of Teachers and Teacher Educators, 2023)
The present study investigated schools of Educationally Backward Block (EBB) in Mizoram. These schools were situated in Lunglei District under the Tlabung Sub-division in the Southern part of Mizoram close to the Bangladesh border. Secondary School was the main target of the study and four schools were randomly selected. A self-developed case study Proforma and a Checklist for School observation were used to collect data. The study was purely qualitative in nature, and analyses of the schools were done in the light of selected parameters. The teaching-learning process in Educationally Backward Block (EBB) Schools in Mizoram was basically child-centric. Teachers and students were working hard to catch up with others students in different parts of the state. Instead of having some fundamental obstacles in terms of communication between students and teachers, lack of ICT assistance and unavailability of SMDC.